Histogenesis of gastric mucosa in human fetal stomach - Nivedita Roy; Sagnik Roy (Wolters Kluwer Medknow Publications, 2016)
Background and aims: Human fetal stomach starts developing at 4th week of gestational age. The precise knowledge of development of gastric mucosa is important for better understanding, diagnosis and treatment of different clinical conditions like Intestinal metaplasia, pernicious anaemia, heterotopic pancreatic tissue, atrophic gastritis etc. All these conditions are related to anomalous histogenesis of stomach. The aim of the study was to find out development of lining epithelium, gastric pits and glands and their ratio, time of appearance of different gastric mucosal cells in different weeks of gestation. Materials and methods : Sixty three normal fresh aborted fetuses were collected from obstetrics and gynaecology department of Regional Institute of Medical Sciences, Imphal. The fetuses were dissected and stomach was gently taken out, fixed in 10% normal saline and Bouin's fluid followed by processing of the tissue. Staining was done with Haematoxylin and Eosin and Masson's Trichrome. Results : The lining epithelium of stomach was seen to be simple cuboidal at 15 to 16 weeks which changed to columnar at 17th week of age. Gastric pits were seen to be very shallow in fundic part at 15th week and attained adult pattern by 28th week where as in pyloric part pits were deeper than fundic part from 17th week onwards. Parietal cells were first appreciated by 19th-20th week, chief cells and mucous neck cell were first seen by 25th-26th and 23rd-24th weeks respectively. Entero- endocrine cells were seen from 26th week onwards. No finding was suggestive of intestinal metaplasia or heterotopic pancreatic tissue or any other histogenetic anomaly. Conclusion : Very few studies have been conducted so far regarding histogenesis of human fetal stomach in India. The present study is expected to supplement known data and knowledge regarding histogenesis of human fetal stomach and help in diagnosis and treatment of related congenital anomalies.